2014
DOI: 10.1088/1742-5468/2014/12/p12009
|View full text |Cite
|
Sign up to set email alerts
|

Quench action approach for releasing the Néel state into the spin-1/2 XXZ chain

Abstract: The steady state after a quantum quench from the Néel state to the anisotropic Heisenberg model for spin chains is investigated. Two methods that aim to describe the postquench non-thermal equilibrium, the generalized Gibbs ensemble and the quench action approach, are discussed and contrasted. Using the recent implementation of the quench action approach for this Néel-to-XXZ quench, we obtain an exact description of the steady state in terms of Bethe root densities, for which we give explicit analytical expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
180
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(189 citation statements)
references
References 120 publications
7
180
2
Order By: Relevance
“…The question of thermalization can then reduce to the question of how narrow in energy the overlap distribution is. Recent work (such as the "quench action" approach [82][83][84][85][86][87][88] and an approach based on linked-cluster expansions [89,90]) has formulated calculations of long-time expectation values directly in the thermodynamic limit, thus avoiding the explicit calculation of overlaps in finite-size systems.…”
Section: O(t) = ψ(T)|o|ψ(t) = ψmentioning
confidence: 99%
See 1 more Smart Citation
“…The question of thermalization can then reduce to the question of how narrow in energy the overlap distribution is. Recent work (such as the "quench action" approach [82][83][84][85][86][87][88] and an approach based on linked-cluster expansions [89,90]) has formulated calculations of long-time expectation values directly in the thermodynamic limit, thus avoiding the explicit calculation of overlaps in finite-size systems.…”
Section: O(t) = ψ(T)|o|ψ(t) = ψmentioning
confidence: 99%
“…By taking the thermodynamic limit of the results of Ref. [122], it was possible to investigate the long-time limit in quenches to the antiferromagnetic gapped phase ∆ f > 1 [84][85][86] and also to the isotropic point ∆ f = 1 [86], using the quench action approach [82]. However, extracting all the overlaps for large but finite chains by means of the exact formulas of Refs.…”
Section: The Modelmentioning
confidence: 99%
“…The GGE is expected to describe the equilibration of local observables after a quantum quench in an integrable system by taking into account all constraints associated to its conserved charges [3,5,. While in its standard form it was constructed exclusively out of local conserved charges [28,29], it has been recently shown that quasi-local charges must also be included [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. This gives an answer to the fundamental question of how much information about the initial state survives in the final values of local observables.…”
mentioning
confidence: 99%
“…the one reported in Fig. 1) in the GGE and for infinite time can be expanded close to the Δ = ∞ point obtaining [66] …”
Section: -P4mentioning
confidence: 84%
“…From these overlaps, the infinite time limit of the evolution has been explicitly calculated for the Neel state in Ref. [65,66] and for the dimer state in [67], again exploiting the representative state approach of Ref. [52].…”
Section: -P4mentioning
confidence: 99%